Pengaruh Perceived Quality, Duration to Deliver, Perceived Shipment Fee, Review And Rating Terhadap Intention To PurchaseProduct Fashion In Tiktok Shop( Management Student of University Teuku Umar) - Fadhillah, Risa (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the influence of Perceived Quality, Delivery Duration, Perceived Shipment Fee, and Reviews and Ratings on the Intention to Purchase Fashion Products on TikTok Shop among Management students at Teuku Umar University. The research is motivated by the growing phenomenon of TikTok Shop as a social commerce platform that integrates entertainment with shopping activities. A quantitative research method with a survey approach was employed. The population consisted of all active Management students at Teuku Umar University, totaling 628 students. A sample of 86 respondents was determined using the Slovin formula. Data analysis techniques included descriptive analysis, validity and reliability tests, classical assumption tests, multiple linear regression analysis, as well as t-tests and F-tests to examine the research hypotheses, utilizing the Statistical Package for the Social Sciences (SPSS) version 25. The partial t-test results indicated that the variables Perceived Quality (X1) and Reviews and Ratings (X4) had a positive and significant effect on Purchase Intention, with significance values of 0.025 and 0.000, respectively. This suggests that good product quality perception and positive consumer reviews and ratings can enhance the intention to purchase fashion products on TikTok Shop. Meanwhile, the variables Delivery Duration (X2) and Perceived Shipment Fee (X3) did not show a significant effect. Furthermore, the simultaneous F-test results revealed that all four independent variables collectively had a significant effect on Purchase Intention, with an F-value of 21.291. The Adjusted R² value of 0.488 indicates that 48.8% of the variation in Purchase Intention can be explained by the four independent variables, while the remaining 51.2% is influenced by other factors outside the scope of this study. The study concludes that Perceived Quality and Reviews and Ratings are the dominant factors shaping students’ purchase intentions toward fashion products on TikTok Shop. Therefore, sellers are advised to maintain product quality and encourage customers to provide positive reviews and ratings to enhance trust and purchase intention on the platform. Additionally, attention should be given to Delivery Duration and Perceived Shipment Fee to improve the overall shopping experience for consumers.